Relationship between Pulse Wave Velocity and Myocardial Work in untreated hypertensive patients with preserved LVEF. (3rd October 2022) - Lofrumento, F; Mandraffino, G; Trimarchi, G; Mancinelli, A; Restelli, D; De Sarro, R; Sinicropi, D; Cinquegrani, M; Cusma-Piccione, M; Manganaro, R; Recupero, A; Di Bella, G; et al.
Abstract: Introduction: Hemodynamic interaction between left ventricular (LV) and arterial system is a key determinant of cardiovascular performance. The non-invasive carotid-femoral Pulse Wave Velocity (PWV), obtained with applanation tonometry, is considered the most precise way of estimating arterial stiffness. The LV myocardial work (MW), based on non-invasive LV pressure-strain loop (PSL), is a new promising tool to assess LV function. Purpose: The aim of the study was to evaluate the correlation between PWV and MW parameters in a population of non-hypertensive and newly diagnosed untreated hypertensive people. Material and methods: 50 people (M=30), divided in hypertensive (group 1: n=25, 40±8 years) and non-hypertensive (group 2: n=25, 38±9 years), were prospectively enrolled. All underwent conventional transthoracic echocardiography and at the same day carotid femoral PWV was calculated with applanation tonometry (SphygmoCor® XCEL). MW parameters were obtained using 2D Speckle-tracking technique. Results: Comparing the two groups, PWV and Global Work Wasted (GWW) were significantly higher in the hypertensives group (9.44±2.4 vs 7.56±1.1; p=0.001 and 130±2.5 vs 80.60±1.5, p=0.002), as shown in Figure 1, whereas Global Work Efficiency (GWE) and Global Work Constructive (GWC) were significantly lower (94±2.5 vs 95.8±1.2, p=0.003 and 2393±20 vs 2166±18, p=0.02). We found a linear and positive correlation of PWV with GWW (r=0.315, p=0.026), as seen in Figure 2, and a linear and negative correlation of PWV with GWE (r=−0.315, p=0.026). Conclusion: This study highlights the role of PWV and MW evaluation in hypertensives. Higher PWV and GWW could be considered as red flags of myocardial damage suggesting the need of an early appropriate antihypertensive therapy. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): University Ospital G. Martino - Messina